Progress in Modeling of III-Nitride MOVPE. Issue 3 (August 2020) - Dauelsberg, Martin; Talalaev, Roman
Abstract: This review provides an introduction to III-Nitrides MOVPE process modeling and its application to the design and optimization of MOVPE processes. Fundamentals of the MOVPE process with emphasis on transport phenomena are covered. Numerical techniques to obtain solutions for the underlying governing equations are discussed, as well as approaches to describe multi-component diffusion for typical regimes during MOVPE. Properties of common industrial MOVPE reactor types like close spaced showerhead reactors, rotating disk reactors and Planetary Reactors are compared in terms of underlying working principles and generic process parameter dependencies. The main part of the paper is devoted to reviewing gas phase and surface reaction mechanisms during MOVPE. The process design in particular for MOVPE of III-Nitrides is determined by complex gas phase reaction kinetics. Advances in the modeling and predicting of these processes have contributed to understanding and controlling these phenomena in industrial scale MOVPE reactors. Detailed kinetics and simplified surface kinetic approaches describing the incorporation of constituents into multinary solid alloys are compared and a few application cases are presented. Differences in thermodynamic and kinetic properties of multi-layered structures of different compositions such as InGaN, AlGaN can cause enrichment of the adsorbed layer by certain group III atoms (indium in case of InGaN and gallium in case of AlGaN) that translate into specific features of composition profiles along the growth direction. An intrinsic feature of III-nitride materials is epitaxial strain that shows up in different forms during growth and affects both deposition kinetics and material quality. In case of InGaN MOVPE there is a strong interplay between indium content and strain that has direct influence on distribution of material composition in the epitaxial layers and multi-layered structures. Epitaxial strain can relax via different routes such as nucleation and evolution of the extended defects (dislocations), layer cracking and roughening of the surface morphology. Simulation approaches that address coupling of growth kinetics with strain and defect dynamics are discussed and exemplified.